Correction to: Increase of catastrophic health expenditure while it does not have socio-economic anymore; finding from a district on Tehran after recent extensive health sector reform - Mohammad Hassan Kazemi-galougahi; Elham Dadgar; Zahra Kavosi; Reza Majdzadeh (BMC, 2019)
In the original publication of this article [1], the title should be revised as blow: